(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article, the conditions created for young people in our country, especially how they can improve their lives financially by doing business, are widely covered. In particular, large-scale activities are currently being carried out to involve the population in entrepreneurship, in particular, to provide all-round assistance to the implementation of business ideas of young people.